2003
DOI: 10.1002/elan.200302722
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalysis via Direct Electrochemistry of Myoglobin Immobilized on Colloidal Gold Nanoparticles

Abstract: The direct electron transfer between immobilized myoglobin (Mb) and colloidal gold modified carbon paste electrode was studied. The Mb immobilized on the colloidal gold nanoparticles displayed a pair of redox peaks in 0.1 M pH 7.0 PBS with a formal potential of ±(0.108 AE 0.002) V (vs. NHE). The response showed a surface-controlled electrode process with an electron transfer rate constant of (26.7 AE 3.7) s À1 at scan rates from 10 to 100 mV s À1 and a diffusioncontrolled process involving the diffusion of pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
1
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(33 citation statements)
references
References 43 publications
2
28
1
2
Order By: Relevance
“…Whereas, in the mid 1990s, CPEs were modified with colloidal gold, the identical material has been described a few years later as gold nanoparticles (by the same authors; see [182] vs. [183]). Another authors' team has then reported on both terms within one year, including their combination in the only title (see [184] and [185]). Apart from the reasons, it is apparent that such a way of presentation complicates the orientation of further scientists interested in these otherwise valuable and inspiring research activities.…”
Section: Reflection Of New Technologies In the Electrochemistry With mentioning
confidence: 99%
“…Whereas, in the mid 1990s, CPEs were modified with colloidal gold, the identical material has been described a few years later as gold nanoparticles (by the same authors; see [182] vs. [183]). Another authors' team has then reported on both terms within one year, including their combination in the only title (see [184] and [185]). Apart from the reasons, it is apparent that such a way of presentation complicates the orientation of further scientists interested in these otherwise valuable and inspiring research activities.…”
Section: Reflection Of New Technologies In the Electrochemistry With mentioning
confidence: 99%
“…[1,2] Such electrodes demonstrate improved signal-to-noise ratios or enhanced electron-transfer rates between the active site of redox proteins and electrode surfaces, making it an attractive platform to develop potential biosensors and bioreactors. [3,4,5] It also offers a tool to control the electrode properties by adjusting size, shape, and protective monolayers of nanoparticles. [6] Several methods have been developed to bind AuNP to the electrode surfaces using the direct electrocrystallization from the complex gold salts (chlorauric acid (HAuCl 4 ) [7,8] and potassium gold cyanide (KAu(CN) 2 ) [9]).…”
Section: Introductionmentioning
confidence: 99%
“…Gold nanoparticles have been used for coupling to proteins, 1 DNA, [2][3][4] and RNA in various applications like immunoassays, 5,6 detection of analytes [7][8][9][10] and toxic compounds, 11 for nuclear targeting, 12 as carrier agents, 13 and also as enzymes for biosensors. [14][15][16][17][18] The chemisorption of thiol or disulfide-containing compounds to gold lattices is well known and was described, eg, by Nuzzo et al 19 for simple organic thiols and disulfides and, in succession, was used for staining proteins (gold stain) 20 and also thiollabeled DNA or RNA strands. 21 The high sensitivity of the nanoparticle gold staining method can also be used for application in diverse types of biosensors as, eg, for a concanavalin-A biosensor; 22 an open access review is available of Li et al 23 Proteins such as antibodies (Abs) bind very stably to the surfaces of gold particles via intercalation of their sulfur atoms with the gold lattice.…”
Section: Introductionmentioning
confidence: 99%